2007
DOI: 10.1109/tvcg.2007.70530
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Large-Scale Uncertainty in Astrophysical Data

Abstract: Abstract-Visualization of uncertainty or error in astrophysical data is seldom available in simulations of astronomical phenomena, and yet almost all rendered attributes possess some degree of uncertainty due to observational error. Uncertainties associated with spatial location typically vary significantly with scale and thus introduce further complexity in the interpretation of a given visualization. This paper introduces effective techniques for visualizing uncertainty in large-scale virtual astrophysical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…The authors argue that the principle of whitening is easy to understand but getting detail information from it is difficult. Li et al [29] investigated the issue of scale for uncertainty visualization for astrophysical data and used a unified color scheme to represent log-scale distances and percentage errors. They found that participants were able to determine the amount of uncertainty using colors with 96.7% success rate.…”
Section: Perceptual Studies and User Evaluationsmentioning
confidence: 99%
“…The authors argue that the principle of whitening is easy to understand but getting detail information from it is difficult. Li et al [29] investigated the issue of scale for uncertainty visualization for astrophysical data and used a unified color scheme to represent log-scale distances and percentage errors. They found that participants were able to determine the amount of uncertainty using colors with 96.7% success rate.…”
Section: Perceptual Studies and User Evaluationsmentioning
confidence: 99%
“…Strothotte et al [35] used non-photorealistic techniques to present uncertainty of architectural reconstructions. Li et al [21] visualized uncertainty in astrophysical data and Lundstrom et al [24] presented a probabilistic animation method to illustrate uncertainty in medical volume renderings. Lodha et al [22] used sound for the depiction of uncertainty and Cedilnik and Rheingans [4] demonstrated procedural annotation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Coloring or error bars are also be used for the visualization of geometric or positional differences. The main advantage is that visualization can be utilized in both 2D and 3D [19].…”
Section: Visualization Methodsmentioning
confidence: 99%